Discourse Analysis and Humor on Papuan Mop in the Series of “Epen Kah Cupen Toh” - Aldrin Yohanes Ferdinandus; Ounu Zakiy Sukaton; Patrisius Istiarto Djiwandono (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study aims to explore the humor and discourse in Papuan MOP, as depicted in the 2010 YouTube video series "Epen Kah Cupen Toh" (EKCT). Humor reflects different cultures and societal conditions, and MOP is a frequently used humor by Papuan people, making it a unique representation of their lives. The study utilizes qualitative analysis to identify patterns and themes in Papuan MOP humor and discourse. The primary data is collected from the transcription of EKCT video series. Discourse analysis was utilized to further analyze the transcription of videos as the primary data. The findings reveal that the primary type of humor in Papuan MOP is witticism, and the character "Dodi" represents the effects of a lack of education and underdeveloped society in certain areas of the Papuan region. Furthermore, the use of the Papuan Melayu dialect, which emphasizes monosyllabic sounds, adds to the uniqueness of the humor portrayed in the series. The cross-cultural representation in the series also highlights the diverse ethnicities in Indonesia. The study concludes that Papuan MOP humor is closely linked to the social conditions of Papuan people, making it a valuable aspect of their cultural heritage.